Molecular test for chlamydia and gonorrhoea used at point of care in remote primary healthcare settings: a diagnostic test evaluation. (10th May 2018) - Causer, Louise M; Guy, Rebecca J; Tabrizi, Sepehr N; Whiley, David M; Speers, David John; Ward, James; Tangey, Annie; Badman, Steven G; Hengel, Belinda; Natoli, Lisa Jane; Anderson, David A; Wand, Handan; et al.
Abstract : Objectives: A new molecular test for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) (GeneXpert CT/NG) has been demonstrated to be as accurate as conventional nucleic acid amplification tests (NAAT), but performance has not been evaluated in routine primary care, performed at the point of care by clinicians. We aimed to examine its diagnostic performance when used by clinicians in remote community health services in Australia with high prevalences of CT and NG infection. The trial was registered with the Australian and New Zealand Clinical Trials Registry (#12613000808741) Methods: At 12 health services, training was provided to 99 clinicians in the use of the GeneXpert CT/NG assay who tested specimens from all patients undergoing STI screening. Specimens were also sent in parallel for conventional laboratory-based NAATs and the concordance of results was evaluated. Results: Clinicians conducted 2486 tests: CT concordance was 99.4% (95% CI 99.1 to 99.7) with a positive concordance of 98.6% (95% CI 95.9 to 99.7) and negative concordance of 99.5% (95% CI 99.1 to 99.8); NG concordance was 99.9% (95% CI 99.7 to 100.0) with a positive concordance of 100.0% (95% CI 97.5 to 100.0) and negative concordance of 99.9% (95% CI 99.7 to 100.0). Conclusions: In this first study reporting routine point-of-care use of GeneXpert CT/NG by primary care clinicians, we found excellent concordance with conventional NAATs. The use of the GeneXpert CT/NG at the point of care could potentially transform management and control of these infections in many endemic settings, including low/middle-income countries.